2019
DOI: 10.1002/ejp.1458
|View full text |Cite
|
Sign up to set email alerts
|

Delayed effects of attention on pain sensitivity and conditioned pain modulation

Abstract: Background Efficacy of pain modulation is assessed as the difference in pain sensitivity during a painful conditioning, compared to before (conditioning pain modulation, CPM). Attention can be assessed with the Stroop task, in which participants report the number of words on a screen; either congruent or incongruent with the value of the words. Attention away from painful stimuli during CPM enhances the CPM effect. However, it is unknown if attention influences CPM effects when the two are done in sequence. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 65 publications
(150 reference statements)
1
24
2
Order By: Relevance
“…The lack of the painful stimulus on Stroop task performance is likely due to the task's effect on individuals' pain perception (Seminowicz & Davis, 2007;Valet et al, 2004). For example, Hoegh et al (2019) found that the pain intensity scores of healthy individuals during Stroop task sessions with evoked pain were lower than those during sessions without the Stroop task, indicating an analgesic effect of the task due to distraction. RTs in the present study indicated that the Stroop task imposed a greater cognitive load than did the spatial cue task.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of the painful stimulus on Stroop task performance is likely due to the task's effect on individuals' pain perception (Seminowicz & Davis, 2007;Valet et al, 2004). For example, Hoegh et al (2019) found that the pain intensity scores of healthy individuals during Stroop task sessions with evoked pain were lower than those during sessions without the Stroop task, indicating an analgesic effect of the task due to distraction. RTs in the present study indicated that the Stroop task imposed a greater cognitive load than did the spatial cue task.…”
Section: Discussionmentioning
confidence: 99%
“…Attentional focus towards the conditioning stimulus had an additive effect on CPM‐magnitude with application of the CPT at the m. trapezius and CPA, which is in accordance with previous studies (Defrin et al., 2010; Ladouceur et al., 2012). It seems that attention driven analgesia uses partially overlapping mechanisms as those of pain‐driven analgesia (Hoegh et al., 2019) and this might explain the CPM‐effects for these paradigms. Although CPM‐efficacy is usually independent of perceived pain intensity (Nahman‐Averbuch et al., 2016), we found that perceived pain intensity of the conditioning stimulus influenced CPM‐efficacy for DIO at the m. trapezius.…”
Section: Discussionmentioning
confidence: 99%
“…Young adults and middle-aged adults can use cognitively demanding tasks to diverge their attention and self-manage pain to some extent (Valet et al, 2004). Pain sensitivity is decreased with engagement in attention requiring tasks and with the use of environmental distractors (Sloan and Hollins, 2017;Hoegh et al, 2019). However, older adults are limited in this capacity, and chronic pain can impair independent living, a risk factor for physical disability, hospitalization, and death (van der Leeuw et al, 2018).…”
Section: Attentionmentioning
confidence: 99%